Dosimetric comparison and evaluation of different convergence modes in nasopharyngeal carcinoma using VMAT treatment deliveries - Lan,Maoying; Wu,Rui; Deng,Guanhua; Yang,Bo; Zhuang,Yongdong; Yi,Wei; Xu,Wenwei; Sun,Jiancong (PeerJ, 2024)
Background This study investigates the impact of convergence mode (CM) in Eclipse (Varian Medical Systems) on the quality and complexity of volumetric modulated arc therapy (VMAT) plans for nasopharyngeal carcinoma (NPC) patients. Methods We retrospectively analyzed data from 21 NPC patients. For each patient, three VMAT plans with different CM settings (Off, On, and Extended) were created using identical optimization objectives. Plan quality was assessed using indices such as the conformity index (CI) and homogeneity index (HI), as well as evaluating target coverage and sparing of organs at risk (OARs). Complexity was measured by metrics including average leaf pair opening (ALPO), modulation complexity scores for VMAT (MCSv), monitor units (MUs), and optimization time. Dosimetric verification was performed based on the gamma pass rate. Results Different CM settings can generate treatment plans that meet clinical dose objectives for planning target volumes (PTVs) and OARs. The ‘On’ or ‘Extended’ CM settings improved CI and HI for the NPC target volume and reduced OAR doses, especially the mean dose, without compromising target coverage. The ‘Extended’ CM setting produced the most favorable outcomes. ALPO values for CM settings ‘Off’, ‘On’, and ‘Extended’ were 29.1 ± 4.3 mm, 28.6 ± 4.2 mm, and 28.4 ± 4. 2 mm, respectively. MCSv values for these settings were 0.1730 ± 0.0215, 0.1691 ± 0.0204, and 0.1693 ± 0.0208, respectively. MUs were 796.2 ± 110.8 for CM ‘Off’, 798.6 ± 106.1 for CM ‘On’, and 799.7 ± 103.6 for CM ‘Extended’, with no significant differences (p > 0.05). Gamma pass rates for all plans were above 99% (3%/3 and 2%/2 mm), with no significant differences among groups (p > 0.05). The average optimization times for CM settings ‘Off’, ‘On’, and ‘Extended’ were 14.4 ± 3.2, 35.9 ± 8.9, and 145.6 ± 50.3 min, respectively (p < 0.001). Conclusion CM usage can improve the CI and HI of the target volume and decrease the dose to OARs in VMAT plans for NPC patients. This study suggests that CM can be a valuable tool in VMAT planning for nasopharyngeal carcinoma, given adequate planning time.
Keywords: Convergence mode; VMAT; Nasopharyngeal carcinoma; Plan complexity; Radiotherapy; Plan quality